Cationic Dye Degradation and Real Textile Wastewater Treatment by Heterogeneous Photo-Fenton, Using a Novel Natural Catalyst - Sirine Ben Ayed (MDPI AG, 2021)
A photo-Fenton process using a local iron oxide as a natural catalyst was compared to Fenton and UV/H2O2 advanced oxidation processes for degrading crystal violet (CV) dye in aqueous solutions. The catalyst was characterized by transmission electron microscopy (TEM), energy dispersive X-ray microanalysis (EDX), Fourier transform infrared spectroscopy (FT-IR), Raman spectrum, X-ray diffraction (XRD), UV-vis spectroscopy, and Brunauer–Emmett–Teller (BET) analysis. The optical properties proved that the catalyst represents a good candidate for photocatalytic activity. The impact of different parameters (catalyst dose, initial CV concentration, initial H2O2 concentration, pH) on the photo-Fenton efficiency was evaluated. A photo-Fenton process operated under UVC light irradiation, at spontaneous pH, with 1.0 g/L of catalyst and 30 mg/L of H2O2 was the most effective process, resulting in 98% CV dye removal within 3 h. LC-MS and ion-chromatography techniques were used to identify demethylated organic intermediates during the process. Furthermore, a regeneration study of the catalyst showed its stability and reusability (after three treatment cycles, CV dye degradation decreased from 94% to 83%). Finally, the photo-Fenton process was tested in the treatment of real textile wastewater, and the effluent was found to be in compliance with standards for industrial wastewater disposal into sewerage.